Prevalences and Determinants Analysis of Scabies Incidence in Rumak Village - Halid, Idham; Halid, Musparlin; Budi Susilo, Beny Binarto (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2024)
Scabies are a global health problem that affects millions of people around the world, especially those living in densely populated and underprivileged areas. Rumak Village, located in a rural area, is no exception to this problem. Where people often live in crowded conditions, making the transmission of scabies easier. This study aims to analyze the determinants of scabies transmission. This study employed a cross-sectional design to examine the prevention behaviors employed by individuals in Rumak Village to avoid the transmission of scabies, totaling 483 families conducted from January to July 2023. Data collection was done using questionnaires, and data analysis was done using Chi-Square, with a p-value of 0.05 with a 95% confidence interval. The results showed a significant association between hand washing practices, home environmental hygiene, sharing items, and bathing practices with the incidence of scabies in the community, with a p-value of 0.000. Families who do not regularly wash their hands, have less clean environmental conditions, often practice sharing personal items, and bathe 1 time/day have a risk of suffering from scabies in Rumak Village.  Keywords: Determinants, prevalence, scabies